Recommendation System of Component Selection for Aquascape With SMART Method - Sri Melvani Hardi; ivan jaya (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
AbstractThe increasing enthusiasm of aquascape hobbyists is one of the factors in the development of the beauty industry of artificial underwater ecosystems in the aquarium. The aesthetic value offered by aquascape is one of the allures for its connoisseurs. The art of organizing ecosystems in water is a simple definition of an aquascape. The complexity of the arrangement can then be described through the presence of various themes. The selection of tools, flora and fauna, and other ornaments to form a unified ecosystem are things that are of concern so that an ecosystem in artificial water has good aesthetic value and can be categorized in a certain theme. By using a decision support system (DSS) or decision-making system, the results can provide better decisions and minimize the possibility of errors. One method of decision making in the scope of decision support system (DSS) or decision making system is Simple Multi Attribute Rating Technique (SMART), where this method can determine product recommendations based on several product variants offered as a form of marketing analysis. This method is able to provide recommendations for more than one decision and provide results with the best accuracy. System testing was conducted to 50 users and it was found that the recommendation system based on the questionnaire application was able to provide a good percentage of conformity between the user's wishes and the recommendations given. That is, 51% of correspondents rated it very appropriate, 27.5% of correspondents rated accordingly, 19.5% of correspondents rated neutral, and only 2% of correspondents rated it inappropriateKeywords: Aquascape, Decision Support System, SMART, Recommendation